The Effect of Non-penicillin Antibiotic Regimens on Neonatal Outcomes in Preterm Premature Rupture of Membranes - Siegel, Anne M.; Heine, Robert Phillips; Dotters-Katz, Sarah K. (American Journal of Perinatology Reports, 2019)
Objective A 7-day course of a penicillin (PCN) and macrolide is standard of care (SAR) in preterm premature rupture of membranes (PPROM). Data regarding alternative antibiotic regimens are limited. We sought to assess the impact of non-PCN regimens on neonatal outcomes.Study Design Secondary analysis of randomized controlled trial of antenatal magnesium sulfate. Singleton, nonanomalous pregnancies complicated by PPROM at > 24 weeks of gestation receiving the SAR were compared with women receiving a non-β-lactam regimen and a macrolide (NPCR). Primary outcome was a neonatal composite. Secondary outcomes included pregnancy latency, endometritis, and chorioamnionitis.Results A total of 949 women met inclusion criteria; 821(56%) received the SAR and 128(8.8%) received NPCR. Adjusted models did not demonstrate worse outcomes (AOR [adjusted odds ratio] = 0.50; 95% CI [confidence interval]: 0.22–1.11). Neonates receiving SAR were less likely to have bronchopulmonary dysplasia (BPD; p = 0.03) but more likely to have severe necrotizing enterocolitis (sNEC; p = 0.04). Risk for chorioamnionitis and median latency did not differ between groups but women receiving the SAR were less likely to get endometritis (AOR = 0.35; 95% CI: 0.14–0.91).Conclusions In this cohort, receiving NPCR in the setting of PPROM did not impact the overall risk of adverse neonatal outcomes or latency, but did increase the risk of endometritis. Alterations in individual neonatal morbidities suggest follow-up studies are needed.
Keywords: preterm premature rupture of membranes; antibiotics; penicillin allergy; obstetric infectious disease